The Impact of Religious Beliefs on the Architecture of Ancient Iraqi Temples and Ziggurat (The Ziggurat of Babylon as A model) (Journal of the College of Basic Education, 2022)
The topic of religious beliefs is one of the important topics in the field of archaeological and historical studies, as religious beliefs, worship and rituals occupied a large and important space in the life of ancient peoples and left visible effects on their civilizational path. We may not be wrong if we say that the religious aspect was one of the most important factors affecting the civilizations of ancient nations, as it contributes to defining general frameworks for customs, traditions, customs and laws and has an impact on economic, artistic and literary life. No matter how different religions differ and can vary, it can be said in general that they assume the existence of a supreme force or forces in the universe that man always seeks to draw near to them through certain acts of worship and rituals that are held in designated places known as the "Temple" in Mesopotamia civilization.The research dealt with two main axes, the first of which was: the impact of religious beliefs in the architecture of the ancient temple and ziggurat of Babylon, "Tower of Babel", in which the history of building the temple and its famous ziggurat was discussed and documented, and a review of the most important opinions and assumptions that were presented regarding the origin of its name and the correct time date for its construction and renewal by kings and rulers Mesopotamia through different historical eras in the light of cuneiform sources and archaeological evidence revealed by the results of archaeological excavations in the city of Babylon and its adjacent ancient cities in the past century. While the second axis dealt with the Tower of Babel and the city of Bursba (Press Nimrod), in which the dialectical relationship between the Babel Tower and the Ziggurat Press Nimrod was discussed in the city of Bursa. Also, reference was made to the most important woven stories about the Ziggurat of Bursba and its relationship with the Tower of Babel from fictional stories and legendary narratives mentioned in historical and other sources, influenced by what was mentioned in the novels of the book of the Old Testament "the Torah", which raised many questions and controversy among the researchers, specialists and even the general public on The Ziggurat of Bursba is the Tower of Babel. Hence, this study tried to provide some answers to these questions through the use of cuneiform sources, studies and the results of archaeological excavations that took place in the city and its vicinity.